Simulation of the Flowability of Fresh Concrete by Discrete Element Method - Li, Yue; Hao, Ji; Jin, Caiyun; Wang, Zigeng; Liu, Jianglin (Frontiers in Materials, 2021)
The Discrete Element Method (DEM) was used to establish the slump model and J-Ring model of concrete to describe the flow behavior in the slump test and J-Ring test. Then, the contact parameters of particle-particle and particle-geometry for the concrete DEM model, including restitution coefficient, rolling friction coefficient, static friction coefficient and surface energy were measured. In order to avoid the influence of the shape and size of the aggregate, this paper used high-precision glass spheres as the aggregate of the concrete for meso calibration test, slump test and J-Ring test. Comparing the slump DEM model based on the JKR contact model and the determined contact parameters with the concrete slump test result, a very high agreement between the initial stage, the rapid flow stage and the slow flow stage of the Slump flow-Time curve can be found as well as the final slump and slump flow. Moreover, similar to the slump DEM model, the DEM model of the concrete J-Ring test was established to study the passing ability of concrete with outstanding accuracy. Therefore, the concrete DEM model with contact parameters and JKR model can be adopted to study the flow behavior of the fresh concrete.